Optimization of supercapacitor sizing for high-fluctuating power applications by means of an internal-voltage-based method. (15th September 2019) - Pedrayes, Joaquín F.; Melero, Manuel G.; Cano, José M.; Norniella, Joaquín G.; Orcajo, Gonzalo A.; Cabanas, Manés F.; Rojas, Carlos H.
Abstract: The latest advances in the field of supercapacitors (SCs) have made them a feasible alternative to be used in hybrid, energy storage systems. Sizing SCs in such systems is not obvious, especially in the case of banks comprising several series-parallel configurations. In this paper, a new algorithm for sizing a SC bank in high fluctuating power demand applications is proposed. The algorithm utilizes the expected discharge power profile, usually obtained from measurement campaigns, and a set of resistance ( R ) and capacitance ( C ) values of the equivalent circuit of the SC, which are provided by the manufacturer. Instead of yielding specific values for R and C, the method determines the RC limit curve which identifies the area of the RC-plane where the range of acceptable solutions can be found for a particular application. Thus, the internal resistance can be easily included in the design process. The validity of different cell combinations, including those not regarding each series-connected element as a sole cell, can be directly checked with this method, enabling the selection of the most suitable solution from an economic point of view. Highlights: The method is not restricted to the use of single cells in series combination but to any shunt association. The method is valid for the most general case of charge and discharge processes. The algorithm allows easily the designer of the storage system to check the current values. Physical connections can be considered in the SC design to verify if it is valid at different temperatures.